2016
DOI: 10.2147/dmso.s120101
|View full text |Cite
|
Sign up to set email alerts
|

Trends in medication use in patients with type 2 diabetes mellitus: a long-term view of real-world treatment between 2000 and 2015

Abstract: BackgroundDespite the availability of a variety of treatments, many patients with type 2 diabetes mellitus (T2DM) are not achieving glucose control. We analyzed successive waves of the Adelphi Real World Diabetes Disease Specific Programmes (DSPs) to assess treatment patterns reported by primary care physicians (PCPs) and specialists and the effect of treatment on levels of glucose control.MethodsData were collected between 2000 and 2015 in the US and EU5 (France, Germany, Italy, Spain, and the UK). Physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 8 publications
(11 reference statements)
1
71
0
1
Order By: Relevance
“…We and others have reported that DKD is a major risk factor for hypoglycaemia due to multiple factors including reduced renal gluconeogenesis and drug clearance . Although we did not record the year of insulin initiation in these patients, patients with DKD had over 10 years of diabetes when the use of insulin analogues and basal‐bolus regimen were less popular …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We and others have reported that DKD is a major risk factor for hypoglycaemia due to multiple factors including reduced renal gluconeogenesis and drug clearance . Although we did not record the year of insulin initiation in these patients, patients with DKD had over 10 years of diabetes when the use of insulin analogues and basal‐bolus regimen were less popular …”
Section: Discussionmentioning
confidence: 92%
“…30,31 Although we did not record the year of insulin initiation in these patients, patients with DKD had over 10 years of diabetes when the use of insulin analogues and basal-bolus regimen were less popular. 32,33 In this real-world register, more women reported hypoglycaemia than men, after adjusting for confounders. Despite having similar glycaemic control (mean HbA1c 72 mmol/mol [8.7%]), women had a higher BMI by 0.4 kg/m 2 and a higher weight-adjusted TDD for any insulin regimen compared to men.…”
Section: F I G U R E 1 Multivariable Linear Regression Analyses Of Thmentioning
confidence: 94%
“…Similarly, we considered fixed‐dose combinations as 2 different NIADs, but they have been reported to be associated with greater adherence compared to the combination of separate pills, which may impact the need for treatment intensification in some cases. Moreover, differences between general practitioners and endocrinologists must be taken into account, as specialists are more likely to use insulin therapies (eg, in 8.6% and 1.7%, respectively, of patients with poor glycaemic control) and they tend to initiate insulin treatment sooner than primary care physicians . This probably reflects a referral bias, with specialists managing the most advanced and complex patients and, hence, those with the worst glycaemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, differences between general practitioners and endocrinologists must be taken into account, as specialists are more likely to use insulin therapies (eg, in 8.6% and 1.7%, respectively, of patients with poor glycaemic control) 16 and they tend to initiate insulin treatment sooner than primary care physicians. 56 This probably reflects a referral bias, with specialists managing the most advanced and complex patients and, hence, those with the worst glycaemic control. Nevertheless, the SIDIAP database includes prescriptions from both specialists and primary care physicians, with no differentiation of origin.…”
Section: Factors Predicting Intensificationmentioning
confidence: 99%
“…Diabetes mellitus management using pharmacological treatments has become increasingly complex with the variety of agents and treatment guidelines available 5–7. Despite extensive treatment guidelines and a wide array of treatment options from the American Diabetes Association (ADA), the European Association for the Study of Diabetes (EASD)7 8 and the National Institute for Health and Care Excellence,9 the proportion of patients with T2D achieving good glucose control has not increased greatly since 2008 10…”
Section: Introductionmentioning
confidence: 99%